2020
DOI: 10.3389/fendo.2019.00925
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Models of Fibrous Dysplasia/McCune-Albright Syndrome

Abstract: The G s G-protein coupled receptor pathway is a critical regulator of normal bone formation and function. The G s pathway increases intracellular cAMP levels by ultimately acting on adenylate cyclase. McCune-Albright Syndrome (MAS) and fibrous dysplasia (FD) of the bone are two proto-typical conditions that result from increased cellular G s signaling activity. Both are caused by somatic activating mutations in the GNAS gene that encodes for the G s α subunit. FD bone lesions are particularly difficult to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“… 8 In contrast, the expression of the mutation in early progenitor cells residing within the bone marrow stroma leads to a dramatic derangement of bone and marrow architecture and function. 7 , 9 These results are consistent with current knowledge of the biology and activity of bone marrow osteoprogenitor cells. However, the bone marrow stromal cell (BMSC) system is heterogeneous and comprises not only osteoprogenitor cells but also contains progenitors committed to the adipogenic lineage.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“… 8 In contrast, the expression of the mutation in early progenitor cells residing within the bone marrow stroma leads to a dramatic derangement of bone and marrow architecture and function. 7 , 9 These results are consistent with current knowledge of the biology and activity of bone marrow osteoprogenitor cells. However, the bone marrow stromal cell (BMSC) system is heterogeneous and comprises not only osteoprogenitor cells but also contains progenitors committed to the adipogenic lineage.…”
Section: Introductionsupporting
confidence: 87%
“…However, significant insights were provided by transgenic mice in which a gain of function mutation of Gsα was expressed in a ubiquitous and constitutive manner, 7 or at specific differentiation stages of maturation within the osteogenic lineage. 8 , 9 Overall, these models demonstrated that dysregulated activity of Gsα in differentiated osteoblasts stimulates bone formation but does not affect the bone marrow microenvironment. 8 In contrast, the expression of the mutation in early progenitor cells residing within the bone marrow stroma leads to a dramatic derangement of bone and marrow architecture and function.…”
Section: Introductionmentioning
confidence: 85%
“…embryonic stage (22). The mutated GNAS gene to the activation of the TSH/G protein pathway and the subsequent elevated intracellular adenosine 3',5'-cyclic monophosphate level (23,24). Interestingly, for patients who had the typical triad, mutations of the GNAS gene were detected in 46% of the peripheral blood samples of the patients, while in patients with two or one symptom, this number dropped to 21% and 8%, respectively (25).…”
Section: Figurementioning
confidence: 99%
“…In MAS there is an increased activity of Gs protein signaling, caused by an acquired somatic gain-of-function mutation in the GNAS gene encoding its alpha subunit. G protein coupled receptors (GPCRs) participate in multiple cellular pathways, including some that have been identified as regulators of osteoblast formation and function, influencing bone formation and homeostasis [2,3]. The most accepted models and theories affirm that the mutation is postzygotic, explaining the mosaicism that characterizes the disease, also justified by the ubiquity of the protein in the affected tissues, making the range of extension and severity of its manifestation variable [2,3].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%